MHD natural convective flow of a polar fluid with Newtonian heat transfer in vertical concentric annuli. Issue 1 (31st December 2022) - Panigrahi, Lipika; Panda, J. P.; Dash, G. C.
ABSTRACT: A fully developed laminar free convective flow of polar fluid between two concentric vertical cylinders has been considered. The outer surface of the inner cylinders is subjected to Newton's law of heat transfer in the presence of an adjustable transverse magnetic field. The magnetic lines of force interact with conducting flowing fluid to generate a force act-at-a-distance (control input). The analytic solutions of the governing equations are obtained in the form of modified Bessel function. The important findings are: Newtonian heating/cooling as well as vortex viscosity reduce the velocity distribution; micro-rotation and linear velocity having opposite signs have an experimental bearing; magnetic force, act-at-a-distance, a control input reduce the primary flow which may have a therapeutic application; vortex viscosity is favourable for generating low skin friction coefficient; Reynolds analogy holds good with respect to the annular spacing. Most importantly, high Newtonian heating of the bounding surface may lead to back flow as well as instability to flow and heat transfer processes.